A RARE COMPLICATION OF VENTRICULOPERITONEAL SHUNT: GASTRIC PERFORATION - Bemora, Joseph Synèse; Song, Miraulle Tien Yu; Rakotondraibe, Willy Francis; Ratovondrainy, Willy; Rabarijaona, Mamiarisoa; Andriamamonjy, Clément (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2019)
We report the case of a girl aged 16 months who were admitted in neurosurgery department of the CHU-JRA in November 2018 for dysfunction of a mechanical type ventriculoperitoneal bypass valve. This child presented a hydrocephalus communicating postmeningitic with quadriventricular dilatation since her 7th month. A ventriculoperitoneal shunt has been established. Subsequently, there was an externalization like complication of the distal catheter in the oral cavity due to gastric perforation (confirmed by radiography) at 09 months postoperative. She was operated in emergency to remove the system and replace a shunt with a simple operation.